Psycholinguistic Studies: Strategies for Acquiring Arabic Vocabulary in Preschool Children - Dahlia, Iis; Azzahra, Luthfi Qolbi; Setiyawan, Agung (STIQ Amuntai, 2024)
The purpose of this study is to find out the strategy of acquiring Arabic vocabulary in preschool children. The method used in this study is a qualitative method, with a library research approach. The data collection technique used is in the form of documentation techniques. Data analysis techniques with a descriptive-analytical approach. by using the content analysis method. The data sources in this study are references and guidelines related to the problem being researched as literature data. The results of this study show that there are seven strategies that can be applied to acquire Arabic vocabulary in preschool children, including: First, contextual learning strategies. Second, image-based vocabulary acquisition strategies. Third, vocabulary acquisition strategies by singing and rhyme. Fourth, vocabulary acquisition strategies with illustrated stories. Fifth, vocabulary acquisition strategies are based on language games. Sixth, vocabulary acquisition strategies with creative activities, and Seventh, vocabulary acquisition strategies with social interaction. Hopefully, this research can help future research and these strategies can be applied in learning for the acquisition of Arabic vocabulary in preschool children.